Unshackling Our Youth through Love and Mutual Recognition: Notes from an Undergraduate Class on School Discipline Inspired by Ta-Nehisi Coates and bell hooks - Gene Fellner; Mark Comesañas; Tahjuan Ferrell (MDPI AG, 2024)
This research essay challenges educators to embrace mutual recognition when interacting with students. Our data are the words of the young people who participated with us in one particular undergraduate class on school discipline at Rutgers University in Newark, New Jersey, in the United States in the fall of 2022. Tahjuan, who had been our student in the 7th grade in 2011, co-taught the class with us. In writing this essay and in teaching the class, we were inspired by a short passage from Ta-Nehisi Coates about the shackling young people of color endure and another, by bell hooks, that proposes mutual recognition as a teaching practice that can loosen those shackles. Most saliently, this essay is inspired by the youth we work with who, without reading either Coates or hooks, embody Coates' experience and hooks' wisdom. Though we invited and compensated these particular youth to join us in the class as co-teachers and participants, we believe they are broadly representative of the adolescent students we have worked with over the last 15 years in Newark. All the young people quoted in this article have reviewed what we have written and approved its publication. Tahjuan has agreed to include his name as a co-author.